Appeals against customer actions in the public procurement process: features in Ukraine and other countries - Cheban, Y.Y.; Pisochenko, T.S.; Miroshyn, N.W. («Академик Е.А. Бөкетов атындағы Карағанды университеті» КЕАҚ баспасы, 2020)
Abstract: the article considers the components and sequence of the process of appealing the actions of the customer in the process of public procurement in Ukraine. Terms, grounds, conditions, features of payment and possible options for resolving appeals are indicated. The main aspects of the antitrust authorities of some countries are reviewed.
Keywords: public procurement; participant; customer; decision; appeal; complaint; appellate body